Anti-ceramide antibody and sphingosine-1-phosphate as potential biomarkers of unresectable non-small cell lung cancer - Lilla Bűdi; Dániel Hammer; Rita Varga; Veronika Müller; Ádám Domonkos Tárnoki; Dávid László Tárnoki; Martina Mészáros; András Bikov; András Bikov; Péter Horváth (Pathology and Oncology Research)
ObjectivesSpingosine-1-phosphate (S1P) and ceramides are bioactive sphingolipids that influence cancer cell fate. Anti-ceramide antibodies might inhibit the effects of ceramide. The aim of this study was to assess the potential role of circulating S1P and anti-ceramide antibody as biomarkers in non-small cell lung cancer (NSCLC).MethodsWe recruited 66 subjects (34 controls and 32 patients with NSCLC). Patient history and clinical variables were taken from all participants. Venous blood samples were collected to evaluate plasma biomarkers. If bronchoscopy was performed, bronchial washing fluid (BWF) was also analyzed. We measured the levels of S1P and anti-ceramide antibody with ELISA.ResultsS1P levels were significantly higher in the NSCLC group (3770.99 ± 762.29 ng/mL vs. 366.53 ± 249.38 ng/mL, patients with NSCLC vs. controls, respectively, p < 0.001). Anti-ceramide antibody levels were significantly elevated in the NSCLC group (278.70 ± 19.26 ng/mL vs. 178.60 ± 18 ng/mL, patients with NSCLC vs. controls, respectively, p = 0.007). Age or BMI had no significant effect on anti-ceramide antibody or S1P levels. BWF samples had higher levels of anti-ceramide antibody (155.29 ± 27.58 ng/mL vs. 105.87 ± 9.99 ng/mL, patients with NSCLC vs. controls, respectively, p < 0.001). Overall survival (OS) was 13.36 months. OS was not affected by anti-ceramide antibody or S1P levels.ConclusionHigher levels of S1P and anti-ceramide antibody were associated with active cancer. These results suggest that sphingolipid alterations might be important features of NSCLC.